Inovação aberta no setor de tecnologia da informação no Brasil - Silva, Márcia Aparecida Vieira (2013)
This dissertation sought to identify the results from the innovation open process and its contribution to the development of new markets, considering the achievement of competitive advantage. The study reviews the concepts of competitive advantage, business strategies, market development, information technology, innovation and open innovation. The research was qualitative exploratory. The key element information was obtained by semi-structured interviews. Six managers from software producer companies were interviewed and also a consulting firm in the field of information technology that have adopted the model of open innovation. The technique of content analysis was used for the processing and interpretation of the collected data, according to the procedures recommended by Bardin (2007). As a result the survey showed that the benefits, among others, are related to increased productivity, reduced risks, cost sharing, responsiveness, product development, compliance to the deadline. The delta model was utilized to identify the software producer companies and consulting firm that has a focus on relationship customer, that offers differentiated solutions. As the contribution of the open innovation process, the model facilitates the penetration and market development.